Helicobacter pylori Antibodies and Iron Deficiency in Female Adolescents - Sandström, Göran (PLoS One, 2014)
OBJECTIVE: Iron deficiency (ID) is a common clinical problem worldwide, affecting primarily females. Helicobacter pylori (HP) infection has been shown to be associated with ID. The objective of this study was to define the prevalence of HP antibodies in female adolescents, and to find out if there was a correlation between HP infection and ID. The secondary aim was to study if regularly performed sporting activity, have any association to HP infection, in itself. DESIGN: A controlled clinical trial. SETTING: A senior high school in Gothenburg, Sweden. SUBJECTS: All female athletes at a senior high school for top-level athletes were offered to take part, and 56 athletes took part in the study. The control group consisted of a random sample of age-matched non-athlete students of which 71 entered the study. MAIN OUTCOME MEASURES: Iron deficiency (ID) and iron deficiency anaemia (IDA) were defined by the use of levels of haemoglobin, serum iron, total iron-binding capacity, transferrin saturation, and serum ferritin, as previously described. HP IgG-antibodies were detected by ELISA. RESULTS: 18 of 127 (14%) adolescent females had antibodies against HP. Only 3% had IDA, while 50% had ID. In total, 66% of the HP positive females had ID compared to 48% of the negative females (p = 0.203). No correlation between sporting activity and HP infection was found. Regarding ethnicity, 11/28 of subjects from medium-high risk areas were HP-positive, compared to 7/99 coming from low-risk areas (p<0.001). CONCLUSION: The main finding of this study is that the prevalence of HP IgG antibodies was 14% in adolescent females. We could not find any difference regarding frequency of ID and IDA, between HP positive and negative individuals. Ethnicity is of great importance for the risk of HP infection, while sporting activity itself seems to have no association to HP-infection.